Test Case Generation Framework for Client-Server Apps: Reverse Engineering Approach - Demircioglu, Emine Dumlu; Kalipsiz, Oya (SPRINGER INTERNATIONAL PUBLISHING AG, 2020)
In this paper, the message-driven test case generation framework is proposed for client-server architecture systems which are communicated with each other by using API messages. Basically proposed framework automatically generates test cases, which are extracted with reverse engineering mechanism from captured network packets between client-server communications over networks. We propose a novel approach to record packets for regression testing. The studying is motivated due to the fact that there is a lack of regression test automation framework in a specific domain: client-server apps which uses API messages for the communication, such as financial applications, banking applications, trading systems, real-time apps. Our approach supports the reuse of test cases and will ensure 100% automation from test case generation to execution in API regression testing for client-server applications. Our work reports the significant reuse capability and reduction of effort on a real-word financial system example.
Keywords: Software testing frameworks; Automation testing; API testing; TEST AUTOMATION; Computer Science; Mathematics